Implementasi UndangUndang Nomor 22 Tahun 2022 tentang Pemasyarakatan dalam Pelayanan Administrasi Warga Binaan di Rumah Tahanan Negara Kelas IIB Kraksaan - Varian Zihni Kasyira; Muhammad Dluha; Ach. Syamsul Askandar (Jurnal Hukum Lex Generalis, 2026)
This research aims to analyze the implementation of Law Number 22 of 2022 concerning Corrections in the administrative services for inmates at the Class IIB State Detention Center of Kraksaan, specifically regarding the fulfillment of administrative rights, such as legal status recording, sentence calculation and the granting of remissions, assimilation and social integration. The method employed is empirical legal research with a socio-legal approach, utilizing interviews, observations and documentation. The findings indicate that the implementation of these provisions has not been optimal due to the persistent gap between legal norms (de jure) and field practices (de facto). Normatively, Law Number 22 of 2022 guarantees professional, transparent and accountable administrative services; however, in practice, obstacles such as data processing delays, inaccurate administrative recording, limited personnel, a lack of human resource competence and the incomplete digital integration of the correctional information system remain. These conditions result in the suboptimal fulfillment of inmates' administrative rights and potentially lead to legal uncertainty. Efforts to overcome these challenges include enhancing officer competence through technical correctional administration training, strengthening internal supervision and developing information technology-based administrative systems. Operationally, it is necessary to accelerate the digitalization of administrative services, increase competent human resources, formulate more effective Standard Operating Procedures (SOPs) and conduct regular evaluations of service quality.